Evaluation of Antihypertensive Effect of Shobhanjana and Patoladi Yoga in Uninephrectomy and DOCA Induced Hypertension in Wistar Rats - Dawane JS; Khatavkar PS; Pandit VA; Mate VH (International Journal of Pharma and Bio Sciences, 2020)
Hypertension is the most common chronic non communicable disorder. Most of the patients are asymptomatic and accidently diagnosed with hypertension. Long term raised BP (Blood pressure) results in various cardiovascular complications. Our aim is to evaluate the antihypertensive effect of Shobhanjana and Patoladi yoga in uninephrectomy and DOCA induced hypertension in wistar rats and to study its effect on biochemical parameters. Wistar rats of either sex weighing 200-250 gms were used for the study. Uni-nephrectomy was carried out under all aseptic precautions followed by daily ceftriaxone 200 mg/kg for five days. From the sixth day drinking water was replaced by 1% NaCl along with DOCA (Deoxycorticosterone acetate) subcutaneously in the dose of 20 mg/kg twice a week for four weeks. Hypertensive animals were randomly divided into five experimental groups. Test animals were given drug treatment orally and daily for 15 days, positive control group received Enalapril 10 mg/kg. Control and disease control group were treated with saline. Measurement of systolic, diastolic and mean BP was carried out on day 0, 7 and day 15. Blood collected for biochemical analysis on day 15. Significant decrease in systolic, diastolic & mean blood pressure was seen on day 7 & 15 with Shobhanjana (P < 0.01) and Patoladi yoga (P < 0.01) and Enalapril group (P < 0.01) but combination (S+P) did not show synergistic effect. Patoladi yoga (P < 0.001) was more effective than Shobhanjan (P < 0.05) and Enalapril (P < 0.01) in reducing cholesterol and Triglycerides. Shobhanjana and Patoladi yoga both showed anti-hypertensive activity comparable to Enalapril.